EKSTRAKSI BAKTERI ASAL EKTOMIKORIZA SEBAGAI AGEN ANTAGONIS PENYAKIT TANAMAN FUSARIUM - IG. SEPTRIALDY SALEDA MALIN; NUNANG LAMEK MAY; MUTAKIM (JURNAL KEHUTANAN PAPUASIA, 2020)
Unbalanced interaction between plant and biotic or abiotic components is one of the sources to accelerate the presence of disease. The purpose of this study was to obtain a number of bacteria from Scleroderma citrinum extraction which was describing bacteria morphology, and the observed response of the potential bacteria S. citrinum as antagonists against the disease of Fusarium sp. The results obtained 7 species bacteria from S. citrinum ectomycorrhiza which had the ability to inhibition of different Fusarium sp., diseases. In addition, the 7 types of bacteria S. citrinum had different morphology. Bacterial morphology can be described based on their shapes, edges, colors, and surfaces. The result of the antagonistic test of bacterial isolate Scl 7 was suspected and had the potential to inhibit Fusarium sp., pathogen, in which it can be seen from the highest percentage from the percentage of inhibition of 41.11%. From the study, it has been observed that no visible exploitation by bacteria S. citrinum as the antagonist against Fusarium sp. Therefore, bacteria S. citrinum was suspected to contain antibiosis and competition (nutrient competitor) characteristics.